The Influence of Student's Learning Motivation And Extracurricular Activities on Physical Education Learning Achievement - Sopiyanto, Sopiyanto; Supriadi, Dedi; Ishak, Muchamad; Sobarna, Akhmad (International Journal of Business, Law, and Education, 2024)
This study investigates the impact of student learning motivation and extracurricular activities on Physical Education learning achievement among students at SDN Ciangir 1, Tangerang Regency, using a correlational method. Cluster random sampling was applied, involving 28 fifth-grade students. Questionnaires measured learning motivation, while documentation assessed extracurricular activities and PE learning achievements. Correlation analysis revealed a significant positive correlation between learning motivation (X1) and PE learning achievement (Y), with a coefficient of 0.474. Similarly, a positive correlation was found between extracurricular activities (X2) and PE learning achievement (Y), with a coefficient of 0.423. Additionally, the correlation between learning motivation (X1) and extracurricular activities (X2) on PE learning achievement (Y) was significant, with a coefficient of 0.527. These findings confirm a notable influence of learning motivation and extracurricular activities on PE learning achievement among students at SDN Ciangir 1, Tangerang Regency.